Therapeutic efficacy of pelvic kinesiotherapy in women with stress urinary incontinence – An integrative review (Research, Society and Development, 2022)
Objective: Investigate the therapeutic evidence of pelvic kinesiotherapy in women with stress urinary incontinence and the most used protocols. Methodology: This is an integrative and exploratory review in the Scielo, BVS, PUBMED and LILACS databases, from 2015 to 2021. Results: We excluded 1,767 articles after using filters in the databases. The remaining 253 were evaluated by the title, of which 191 were excluded because they did not answer the guiding question. Of the 62 elected by the title, 25 were selected by the abstract, where 7 were excluded due to repetition in the databases, remaining 18 articles that were read in full. After this analysis, 4 studies were excluded because they did not meet the eligibility criteria, thus 11 scientific articles were included in the present integrative review. Conclusion: In the studies analyzed, pelvic kinesiotherapy proved to be an effective method for the treatment of stress urinary incontinence, although there is no consensus in the literature about a standardized protocol. However, when performed in a supervised manner, they are able to promote better results.